Educational psychology : learning to be a problem solver - Wakefield, John F., 1952- (Boston : Houghton Mifflin, 1996)
This book is divided into four parts: Goal setting; Student characteristics; Approaches to learning; Evaluating learning.
Keywords: Education; Teaching; Educational psychology; Learning, Psychology of; Educational psychology; Teaching -- Psychological aspects